Mapping Air Pollution and Respiratory Health: A GEE-Based Study on CO and NO₂ Exposure and ARI Incidence - Agung Biworo (Jurnal Publikasi Kesehatan Masyarakat Indonesia, 2025)
Banjarmasin, a city in South Kalimantan, faced significant challenges in 2024 due to the dual impacts of El Niño and traditional land-clearing activities, leading to widespread forest and land fires. These fires emit harmful air pollutants, notably carbon monoxide (CO) and nitrogen dioxide (NO2), thereby increasing the risk of Acute Respiratory Infections (ARI) among the population. This study was conducted to analyze the correlation between the concentration of these air pollutants and the incidence of ARI in Banjarmasin throughout 2024. Employing a retrospective research method, data on ARI cases were sourced from the Banjarmasin City Health Office. CO and NO2 concentrations were analyzed using the Google Earth Engine (GEE) with Sentinel-5P satellite imagery and subsequently visualized using ArcGIS. The linear regression test revealed that CO levels showed no significant association with ARI incidence (p = 0.552), accounting for only 22.69% of the variance. Similarly, NO2 levels were not significantly linked to ARI rates (p = 0.1163), accounting for only 3.65%. The findings suggest that, despite the presence of air pollutants from land fires, CO and NO2 have only a weak influence on the incidence of ARI in Banjarmasin.